Using DryadLINQ for Large Matrix Operations - McSherry, Frank; Rodeheffer, Tom (Microsoft Technical Report, 2011)
DryadLINQ is a system that facilitates the construction of distributed execution plans for processing large amounts of data on clusters containing potentially thousands of computers. In this paper, we explore how to use DryadLINQ to perform basic matrix operations on large matrices.